Trichinella-induced immunomodulation: Another tale of helminth success - F. Bruschi; D.S. Ashour; A.A. Othman (Food and Waterborne Parasitology, 2022)
Trichinella spiralis is a unique parasite in that both the adults and larvae survive in two different intracellular niches in the same host. The immune response, albeit intense, is highly modulated to ensure the survival of both the host and the parasite. It is skewed to T helper 2 and regulatory arms. Diverse cells from both the innate and adaptive compartments of immunity, including dendritic cells, T regulatory cells, and alternatively activated macrophages are thought to mediate such immunomodulation. The parasite has also an outstanding ability to evade the immune system by several elaborate processes. The molecules derived from the parasites including Trichinella, particularly the components of the excretory–secretory products, are being continually identified and explored for the potential of ameliorating the immunopathology in animal models of diverse inflammatory and autoimmune human diseases. Herein we discuss the various aspects of Trichinella-induced immunomodulation with a special reference to the practical implications of the immune system manipulation in alleviating or possibly curing human diseases.